2013
DOI: 10.1111/bjh.12580
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐apoptotic TP53 homolog TAp63 is repressed via epigenetic silencing and B‐cell receptor signalling in chronic lymphocytic leukaemia

Abstract: Summary Chronic lymphocytic leukaemia (CLL) is an accumulative disorder marked by deficient apoptosis. The TP53 homolog TAp63 promotes apoptosis and chemosensitivity in solid tumours and its deregulation may contribute to CLL cell survival. We found that TAp63α was the most prevalent TP63 isoform in CLL. Compared to healthy B cells, TAp63 mRNA was repressed in 55.7% of CLL samples. TP63 promoter methylation was high in CLL and inversely correlated with TP63 protein expression in B-cell lymphoma cell lines. siR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 49 publications
4
35
1
Order By: Relevance
“…Although TP63 gene contains two transcriptional start sites that enable the generation of transcripts containing (TAp63) or lacking (ΔNp63) the N‐terminal transactivation domain, we found that only the TAp63 isoform was expressed in CLL, in line with previous studies . Generally, most CLL cases expressed low levels of TAp63 mRNA and p63 protein in accordance with previous reports, with the striking exception of subset #8, where p63 was overexpressed compared to the majority of other U‐CLL or M‐CLL cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although TP63 gene contains two transcriptional start sites that enable the generation of transcripts containing (TAp63) or lacking (ΔNp63) the N‐terminal transactivation domain, we found that only the TAp63 isoform was expressed in CLL, in line with previous studies . Generally, most CLL cases expressed low levels of TAp63 mRNA and p63 protein in accordance with previous reports, with the striking exception of subset #8, where p63 was overexpressed compared to the majority of other U‐CLL or M‐CLL cases.…”
Section: Discussionsupporting
confidence: 92%
“…While in solid tumors TP63 mainly plays a pro‐apoptotic and tumor‐suppressive role, its role in B cell neoplasia is unclear. Particularly for CLL, the two published studies reported opposing results, variably proposing TP63 as pro‐apoptotic 51 or anti‐apoptotic . In our study TP63 was found consistently differentially methylated and expressed between the two subsets.…”
Section: Discussionmentioning
confidence: 73%
“…CLL cell apoptosis was measured in duplicate as previously described using the ApoScreen Annexin V apoptosis Kit (19). Briefly, cells were resuspended in 150 μl of Annexin V binding buffer containing 1 μl of Annexin V-PE, 1 μl of 7-AAD and 1 μl of CD19- or CD3-FITC mAbs (Southern Biotech, Birmingham, AL) followed by flow cytometry on a FACSCalibur (Becton Dickinson, Palo Alto, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were analyzed by immunoblotting as previously described (19). The following antibodies were used: Bcl-2, Bcl-xL, Bim, phospho-Bim, phospho-IκBα, cleaved PARP, Mcl-1, p65/RelA, p52/p100, XIAP, FOXO3A (Cell Signaling), Bcl2-A1 (Abcam, Cambridge, MA), NEDD8 (Epitomics, Burlingame, CA), p27 (Santa Cruz, Biotechnology, Santa Cruz, CA), Noxa (Imgenex, San Diego, CA), β-actin (Sigma Aldrich), horseradish peroxidase-conjugated anti-mouse and anti-rabbit antibodies (BioRad).…”
Section: Methodsmentioning
confidence: 99%
“…But as is often the case with competitors in the same field: it may be that only their combined efforts will help to overcome the numerous problems associated with drug resistance in cancer treatment. The promising power of RNAi for therapeutic purposes and gives new hope that a potent tool for the reversion of an oncogenic phenotype is now in our hands (Humphries et al, 2013). BCR/ABL protein is considered relatively stable to the antisense attack (half-life, 48 hours), and it is difficult to influence its level by a single application of anti-BCR/ABL substances (Kanduri et al, 2013).…”
Section: Discussionmentioning
confidence: 99%